2021
DOI: 10.4103/1735-5362.323917
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic potential of the isolated fractions from the plants of Rosaceae family in streptozotocin-induced diabetic rats

Abstract: Background and purpose: Diabetes is a group of multifactorial disorders characterized by chronic-elevated blood glucose levels (hyperglycemia). Natural remedies are used as alternative medications to treat diabetes. Here, we tested the protective effect of the plant extracts of the Rosaceae family on improving insulin secretion and repairing the pancreatic beta cells in diabetic rats. Experimental approach: The oligosaccharide fraction was isolated from the Rosaceae fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In among 13 continuous papers, 2 were excluded because they were on Japanese quince [40] and Chinese quince [41]. Two studies were found through manual searching, and finally, 12 were included in our study [12,22,[42][43][44][45][46][47][48][49][50][51][52]. No human experimental or clinical trial was found, and all studies were on animal or in vitro models.…”
Section: Resultsmentioning
confidence: 99%
“…In among 13 continuous papers, 2 were excluded because they were on Japanese quince [40] and Chinese quince [41]. Two studies were found through manual searching, and finally, 12 were included in our study [12,22,[42][43][44][45][46][47][48][49][50][51][52]. No human experimental or clinical trial was found, and all studies were on animal or in vitro models.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that they can be suitable for consumption by individuals with diabetes and young children [ 3 , 4 ]. It is established in a research of Bahrami et al (2021) that the extracts from nectarine and peach improve the insulin secretion and the function of beta cells of the pancreas in trials with rats with diabetes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%